Optimisation of the execution time inspired in Cross Layer design using effective load balancing in a LAN-WLAN environment. (23rd July 2009) - Macias, E.M.; Sanchez, D.; Suarez, A.; Sunderam, V.
A combination of wireless and wired network can be used to improve the execution time of non-scientific applications at a very reduced cost. In previous works we have presented middleware extensions to efficiently adapt the execution of MPI programs to wireless networks. In this paper we present an improvement of our previous middleware to control the availability of the mobile wireless portable computers. We also present a load balancing mechanism inspired in Cross-Layer techniques that allow us to overlap the pre-emptive control of the wireless channel and battery energy level with the data communication and the computation.